Cosplayes' cosplay exploring the connection between real life personas and the cosplayed anime characters - Zalsos, Joshua Kevin L. 1990- (University of the Philippines Diliman, 2014)
"This undergraduate thesis is mainly concerned with the cosplayers' fandom towards heir adored anime characters. It explores the views and opinions of ten (10) youtth cosplayers about how they perceive their dressed characters, how they were able to relate with them and what implications did their fandom have towards their lives. Using the fan identification study which was complied by Cohen, the fandom studies by Grossberg and the Reception Study as explained by Barthes, Iser and Zafra as guides for the researcher to synthesize the data, it was found out that most of the cosplayers do identify with their characters though their experiences in the past or through certain traits and values that they perceive as common to them and the characters. Yet identifying with the characters was not the only factor which made them cosplay. Behind their fandom, there exists an interplay of social, psychological and emotional factors."